Diversidad florística y valor de importancia de un fragmento de bosque primario en el Ciefor, Iquitos - Angulo Ruiz, Pedro Angel (2022)
We have conducted to number of investigations in the Arboretum " HUAYO " but we do not know what is the floristic diversity, so we asked ourselves the question What is the floristic diversity and valued of importance of to fragment of primary forest in CIEFOR", to answer this question we Sep the following objective, to determines the floristic diversity and it valued of importance of to fragment of primary forest", we describes the elements that make up the vertical and horizontal structure of the forest, and its plant diversity; the existing information of the arboteum " HUAYO " was also compiled. The information was processed and analyzed in the Excel spreadsheet in tables and graphs, by values obtained from the Margalet, Simpson and Shannon-Wiener indexes indicates you that they have to high diversity and that there is to difference between the plots; by the index of importance valued, 36 species add up to 151.15% of total the, and there plows 10 species with the highest ecological weight; so through the values obtained from the indexes that these forests it plows diverse among themselves, it is concluded that the floristic diversity of these forests it plows different. The total number of individuals evaluated was 2540 trees with dap? 10 cm, with 391 species and 49 botanical families distributed in 04 density categories: 03 species in high; 18 in medium; 224 in low and 146 in escaza density.